The impact of climate change on maize production: Empirical findings and implications for sustainable agricultural development - Zhang, Zhexi; Wei, Jiashuo; Li, Jinkai; Jia, Yuankai; Wang, Wei; Li, Jie; Lei, Ze; Gao, Ming (Frontiers in Environmental Science, 2022)
Continuous warming climate conditions have triggered numerous extreme weather events, exerting an unprecedented impact on agricultural and food production. Based on the data of 3,050 small farmers engaged in maize planting from 2009 to 2018 and monitored by the National Rural Fixed Observation Point, this study uses the transcendental logarithmic production function model to calculate the impact of temperature, precipitation, and sunshine hours on maize output. Further, considering climate condition heterogeneity, this study analyzes their development potential in China’s five major maize production areas. Results show that temperature and precipitation have a positive impact on maize output, and that insufficient sunshine hour is a problem for maize output. Five major maize production areas are affected by the climate differently, entailing the need for tailored response measures. Land, labor, and material capital input are key factors affecting maize output. Suggestions include strengthening the prediction of temperature, precipitation, and sunshine hours in maize production areas; establishing effective natural disaster prevention systems; optimizing the agricultural production layout and the planting structure based on local conditions; strengthening farmers’ adaptive behavior toward climate change; developing irrigation and water conservation projects; strengthening the protection of cultivated land; and promoting sustainable agricultural development.